Hubungan Tingkat Kecemasan Dengan Lama Hari Rawat Pada Pasien Akut Miokard Infark (AMI) DI Ruang ICVCU RSUD DR. Moewardi Surakarta - Armada Karima; Yuyun Setyorini ((JKG) Jurnal Keperawatan Global, 2017)
Abstract : Myocardial Infarction, Anxiety, Length of Stay. The purpose of nursing care of cardiovascular patients are to repair hemodynamic, to suffice oxygen need and to decrease anxiety. AMI patients who are undergoing treatment can use anxiety and may the length of stay. Research purpose to determine the relationship between the anxiety and length of stay in myocardial infarction patients at ICVCU Dr. Moewardi General Hospital. This study is descriptive analytic correlation using cross sectional approach. The subject is all AMI patients. The sampling technique using in this research is total sampling. A questionnaire was constructed to collect data. The collection data was analyzed by using spearman. Retrieved from 30 respondents, it is the average age of patients with myocardial infarction is 51-65 (63,3%) and the majority of the majority of the male gender with percentage 63,3%. Majority of AMI patients moderate anxiety with percentage 43,3% and long of stay fast with a percentage 56,7%. Analysis of test result obtained probality value 0.41. Based on the analysis it can be concluced that there is a significant relationship between anxiety and length of day in myocardial infarction patient at ICVCU Dr. Moewardi General Hospital Surakarta.